Examining Medial Longitudinal Arch: A Review of Symptom among the Multiparous Pregnant Women - Zil e huma; Khalid, Mehwish; Arooj Fatima; Hassan bin Akram; Zehra Zaman; Basat, Mehran (International Health Review, 2023)
To evaluate the changes in the medial longitudinal arch of the foot in the third trimester of pregnancy among multiparous women, A Cross-sectional observational study was conducted. Women of age 18-30 in 34-38 gestational weeks were included. Those women who were nulliparous, primiparous, flat foot prior to pregnancy, and had undergone through abortion were excluded from the study. The sample was collected by using non-probability purposive sampling and analyzed by SPSS (Statistical Package for Social Sciences). Navicular drop test of the left foot was 36.4% negative and 63.6% positive, whereas for the right foot it was 52.7% negative and 47.3% positive. The study results indicated that the changes in the medial longitudinal arch of the left foot were more evident as compared to the right foot.